Assessment, restoration and reclamation of mining influenced soils - Bech, Jaume; Bini, Claudio; Pashkevich, Mariya A. (Academic Press, 2017)
Assessment, Restoration and Reclamation of Mining Influenced Soils covers processes operating in the environment as a result of mining activity, including the whole spectra of negative effects of anthropopressure and the environment, from changes in soil chemistry, changes in soil physical properties, geomechanical disturbances, and mine water discharges. Mining activity and its waste are an environmental concern. Knowledge of the fate of potentially harmful elements and their effect on plants and the food chain, and ultimately on human health, is still being understood. Therefore, there is a need for better knowledge on the origin, distribution, and management of mine waste on a global level. This book provides information on hazard assessment and remediation of the disturbed environment, including stabilization of contaminated soils and phytoremediation, and will help scientists and public authorities formulate answers to the daily challenges related to the restoration of contaminated land.--Provided by publisher.